Women's Career Choices, Social Norms and Child Care Policies - Francesca Barigozzi; Helmuth Cremer; Kerstin Roeder (Institute of Labor Economics (IZA), 2017)
Our model explains the observed gender-specific patterns of career and child care choices through endogenous social norms. We study how these norms interact with the gender wage gap. We show that via the social norm a couple's child care and career choices impose an externality on other couples, so that the laissez-faire is inefficient. We use our model to study the design and effectiveness of three commonly used policies. We find that child care subsidies and women quotas can be effective tools to mitigate or eliminate the externality. Parental leave, however, may even intensify the externality and decrease welfare.
Keywords: D13; H23; J16; J22; 330; social norms; child care; women's career choices; women quotas; child care subsidies; parental leave